RELATIONSHIP BETWEEN BONE MINERAL DENSITY AND BODY COMPOSITION IN ELDERLY - ALONSO,ANGÉLICA CASTILHO (2018)
ABSTRACT Objective: To evaluate the association between bone mineral density (BMD) and body composition in healthy older adults at different skeletal sites. Methods: We analyzed 87 medical records and BMD along with the body composition of men ranging from 60 to 87 years of age (mean: 68.5, standard deviation: 6.5). Inclusion criteria were normal BMD values (T-score greater than or equal to -1.0) and body mass index within normal or overweight range (18.5 to 29.5 kg/m2). Body composition was evaluated using bone densitometry with dual-energy X-ray absorptiometry (DEXA) in a LUNAR-DPX apparatus. Results: Greater lean mass, fat mass, and soft tissue was associated with better BMD values in older adults, and higher age was associated with poorer BMD. Conclusion: Body composition (lean and fat masses and soft tissue) in older men is positively associated with BMD at all body sites (arms, legs, and trunk). Level of Evidence II; Prognostic studies - Investigating the effect of a patient characteristic on the outcome of disease.